تطبيق الرفيق الدراسي لاضطراب فرط الحركة في تعلم العربية: منظوران عصبي ونفسي تربوي في باميكاسان: Implementing Study Buddy for ADHD Students' Arabic Learning: Neurolinguistic and Psychological Study in Pamekasan - Nur Diana Arifah; Achmad Muhlis; Bakri Muhammed Bkheet Ahmed (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2026)
Inclusive Arabic language learning in Islamic boarding schools faces significant challenges in supporting students with Attention Deficit Hyperactivity Disorder (ADHD), a neurodevelopmental condition that can lead to academic underachievement and social difficulties if unmanaged. Grounded in neurolinguistic and educational psychology perspectives, this study examines the implementation, effectiveness, and advantages of the study buddy technique for improving Arabic competence among students with ADHD at an Islamic boarding school in Pamekasan, Madura. A qualitative case study design was employed, utilising observation, in-depth interviews, and documentation, with data analysed using Miles and Huberman's framework of reduction, display, and verification. The findings reveal that the study buddy technique was implemented through structured stages within a pull-out system, including identifying learning difficulties, presenting material, repetition, correction, reinforcing meaning, and gradual instruction. From a neurolinguistic perspective, this approach effectively stimulated auditory and visual processing, improved learning focus, and reduced anxiety. The study concludes that the study buddy technique is an effective inclusive learning strategy for students with ADHD in Arabic instruction. It is recommended that Islamic boarding schools adopt this technique more widely and that future research include quantitative and experimental designs to measure long-term neuropsychological impacts. Pembelajaran bahasa Arab inklusif di pesantren menghadapi tantangan signifikan dalam menangani siswa dengan Gangguan Pemusatan Perhatian dan Hiperaktivitas (ADHD), suatu kondisi neurodevelopmental yang menyebabkan prestasi akademik rendah dan kesulitan sosial jika tidak ditangani. Berlandaskan perspektif neurolinguistik dan psikologi pendidikan, penelitian ini bertujuan mengkaji proses implementasi, efektivitas, dan keunggulan teknik study buddy dalam meningkatkan kompetensi bahasa Arab pada siswa ADHD di Pesantren Pamekasan, Madura. Penelitian menggunakan desain studi kasus kualitatif dengan observasi, wawancara mendalam, dan dokumentasi, serta analisis data melalui kerangka Miles dan Huberman. Temuan menunjukkan bahwa teknik study buddy diimplementasikan melalui tahapan terstruktur dalam sistem pull-out, meliputi identifikasi kesulitan belajar, penyajian materi, pengulangan, koreksi, penguatan makna, dan instruksi bertahap. Dari perspektif neurolinguistik, pendekatan ini efektif dalam merangsang pemrosesan auditori dan visual, meningkatkan fokus belajar, serta mengurangi kecemasan. Penelitian menyimpulkan bahwa teknik study buddy merupakan strategi pembelajaran inklusif yang efektif bagi siswa ADHD dalam pembelajaran bahasa Arab. Direkomendasikan agar pesantren mengadaptasi teknik ini secara lebih luas dan penelitian selanjutnya menggunakan desain kuantitatif dan eksperimental untuk mengukur dampak neuropsikologis jangka panjang.